Gender violence in the American Southwest (AD 1100-1300) - Martin, Debra L.
1 online resource
Keywords: This volume uses osteobiography and individual-level analyses of burials retrieved from the La Plata River Valley (New Mexico) to illustrate the variety of roles that Ancestral Pueblo women played in the past (circa AD 1100-1300). The experiences of women as a result of their gender, age, and status over the life course are reconstructed, with consideration given to the gendered forms of violence they were subject to and the consequences of social violence on health. The authors demonstrate the utility of a modern bioarchaeological approach that combines social theories about gender and violence with burial data in conjunction with information from many other sources--including archaeological reconstruction of homes and communities, ethnohistoric resources available on Pueblo society, and Pueblo women's contemporary voices. This analysispresents a more accurate, nuanced, and complex picture of life in the past for mothers, sisters, wives, and, captives.